SOME EXACT SOLUTIONS OF FIFTH ORDER EQUATION OF BURGERS HIERARCHY - Unal, I. C. (Editura Bibliotheca-Bibliotheca Publ House, 2019)
In this paper, we implemented an improved tanh function Method for some exact solutions of fifth order equation of Burgers hierarchy. This method is presented by Chen and Zhang.
Keywords: Fifth order equation of Burgers hierarchy; improved tanh function method; exact solutions